On ideas : a philosophical dialogue - Pappas, Nicholas J. (Algora Publishing, 2020)
"A philosophical treatment of ideas, the book presents a philosophical dialogue much in the spirit of classical philosophical dialogues, notably those of Plato and Xenophon. As those authors do in a number of their works, Nick Pappas adopts a light and playful tone to treat a serious topic. This contrast helps bring out the truth, in an approachable style that requires no prior exposure to philosophy and heavy intellectual work"--